An update on Termitomorpha Wasman (Coleoptera: Staphylinidae) including a new species, species redescriptions and geographic extension - Da Silva, Ruan Felipe; Caron, Edilson; Carvalho-Filho, Fernando Da Silva (Zootaxa, 2022)
The diversity of Staphylinidae found in termite nests is remarkable. The subfamily Aleocharinae alone contains more than 650 termitophilous species, with termitophilous tribes such as the Corotocini, which includes the genus Termitomorpha Wasman. Here, a new Termitomorpha species from the Eastern Brazilian Amazon is described. Both Termitomorpha fissipennis (Casey) and T. manni (Seevers) are recorded for the first time in Brazil for the states of Pará and Paraíba. The Termitomorpha species identification key is updated. A distribution map for the species is also provided.